2023
DOI: 10.18564/jasss.5184
|View full text |Cite
|
Sign up to set email alerts
|

The Wisdom of the Small Crowd: Myside Bias and Group Discussion

Edoardo Baccini,
Zoé Christoff,
Stephan Hartmann
et al.

Abstract: The my-side bias is a well-documented cognitive bias in the evaluation of arguments, in which reasoners in a discussion tend to overvalue arguments that confirm their prior beliefs, while undervaluing arguments that attack their prior beliefs. The first part of this paper develops and justifies a Bayesian model of myside bias at the level of individual reasoning. In the second part, this Bayesian model is implemented in an agent-based model of group discussion among myside-biased agents. The agent-based model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…To better accommodate this fact, Baccini et al ( 2023 ) generated a Bayesian model in which myside bias is distributed heterogeneously over populations of deliberating agents. They found that group deliberation generally had a negative effect on a group’s chances of reaching an accurate consensus, except when myside bias is distributed asymmetrically across initially correct and incorrect reasoners.…”
Section: Open-mindedness and Collective Deliberationmentioning
confidence: 99%
See 1 more Smart Citation
“…To better accommodate this fact, Baccini et al ( 2023 ) generated a Bayesian model in which myside bias is distributed heterogeneously over populations of deliberating agents. They found that group deliberation generally had a negative effect on a group’s chances of reaching an accurate consensus, except when myside bias is distributed asymmetrically across initially correct and incorrect reasoners.…”
Section: Open-mindedness and Collective Deliberationmentioning
confidence: 99%
“…In many contexts this is not the case. For instance, hearings in a court of law or in a parliament chamber are not random, and there is a clear protocol that determines who gets to speak at which time” (Baccini et al, 2023 ). As they point out, adversarial deliberation works best when it’s well structured, such that different agents have different roles to play and everyone follows the same procedural protocol.…”
Section: Open-mindedness and Collective Deliberationmentioning
confidence: 99%